SPEAKING ANXIETY AND PSYCHOLOGICAL FACTORS IN ENGLISH LANGUAGE LEARNING (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Speaking anxiety is one of the most significant psychological barriers affecting learners in English Language Teaching (ELT). Despite having adequate knowledge of grammar and vocabulary, many learners struggle to communicate effectively due to emotional and psychological constraints. This article examines the role of speaking anxiety and related psychological factors such as motivation, self-confidence, fear of negative evaluation, and the affective filter in second language acquisition. Using a qualitative approach based on literature analysis, the study identifies the major causes of speaking anxiety and their impact on learners’ communicative performance. The findings suggest that reducing anxiety and fostering a supportive learning environment are essential for improving speaking skills. The article concludes with pedagogical recommendations for minimizing anxiety and enhancing learner confidence in ELT classrooms.